Pengaruh Penerapan Sistem Inaportnet Terhadap Proses Clearance in dan out Kapal pada PT. Kartika Samudra Adijaya - Bagas Yoga Adhitama Setiawan; Indah Ayu Johanda Putri; Antony Damanik; Romanda Annas Amrullah (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Inaportnet or known as Indonesia Port Integrasion is a system that aims to operate and integrate online ship service and licensing activities from related agencies involved in port activities. The purpose of Inaportnet is to assist shipping companies and service users in handling customs clearance and docking ships at Indonesia ports. This study aims to determine the effect of the implementation of the inaportnet system on the process of clearance in and out of ships in PT Kartika Samudra Adijaya Method using simple linear regression analysis. The sample in this study amounted to 30 respondents. Data collection uses questionnaires. The results of this study show that for every 1% increase in the value of the implementation of the inaportnet system, the ship clearance process will increase by 0.250. The regression coefficient is positive, so it can be said that the direction of the influence of the implementation of the inaportnet system (variable X) on the clearance process in and out of the ship (variable Y) is positive. And based on the significance value obtained from the table above, it can be concluded that the variable of the implementation of the inaportnet system (X) affects the variable of the clearance process in and out of the ship (Y).